(untitled) (Revista Argentina de Musicología, 2024)
In this article we present a paradigmatic analysis of the first Movement of the Sonata op. 10 no. 1 by Ludwig van Beethoven. We intend to relate the multiple transformations of the musical material that we have systematically described with the narrative potential that the piece reveals in its temporal development. The first 8 bars of the work respond to the classic period phrase, however, the neutral level analysis reveals how problematic it is to segment this group into smaller units. To afford this problem we have developed two hypotheses for the articulation of the first 8 bars and five hypotheses for the internal segmentation of the first 4 bars and we verified that all of them coexist at different moments of the piece, being the most evident and perceptually relevant, the least repeated and, paradoxically, the less intuitive and perceptually less relevant segmentations have given rise to the generative events with more explanatory power and therefore those with more narrative power. At the end we propose an interpretation of the formal processes described exhaustively within the framework of Eero Tarasti’s existential semiotics.